Common institutional ownership and corporate carbon emissions - Qiang, Ji; Lei, Lei; Wood, Geoffrey; Zhang, Dayong (Wiley, 2025)
There has been a growing interest in comparative work exploring when and why firms embark on green paths. It has been concluded that in national contexts where inter‐firm ties are stronger, progress has been stronger. In turn, this raises questions about the impact of inter‐firm ties within, rather than between, national contexts, and in settings where progress towards renewables has been uneven and contested. Accordingly, we explore how common institutional ownership may foster collaboration among firms within the same industry against climate change. Using a sample of US‐listed firms from 2006 to 2019, we obtain robust evidence that firms with industrial peers that are owned by the same institutional investors have lower carbon emissions. In addition, we find that a threshold exists for which the impact on carbon emissions holds only when firms are commonly connected with a substantial number of peers. The existence of this threshold suggests potential free‐riding issues and highlights the beneficial role of investors in promoting cross‐industry collaboration. Overall, our results highlight the role played by institutional investors in tackling climate issues, with important implications for both climate‐ and antitrust‐related regulations.
Keywords: 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 13 Climate Action; Business & Management; 3505 Human resources and industrial relations; 3506 Marketing; 3507 Strategy, management and organisational behaviour